Busted! the truth about the 50 most common internet myths - Internet Governance Forum Berlin, Germany 25-29 nov; editor Kettemann, Matthias C.; editor Dreyer, Stephan, (Hamburg, Germany: Verlag Hans-Bredow-Institut, 2019)
[With summaries in german, arabic, chinese, french, russian and spanish] informação retirada da capa The book was published in English and German.